Diseñar y aplicar una guía didáctica para el desarrollo de la inteligencia musical en el inter aprendizaje de los niños y niñas del primer año de educación básica de la escuela fiscal mixta “Vicente Rocafuerte” de la parroquia La Victoria cantón Pujilí, en el período lectivo 2011-2012 - Rubio Espinosa, Fátima Paola (2015)
The main objective of this research was to design a teaching guide for the development of musical intelligence and enhance mutual learning of children in the first year of basic education of the Joint Public School Vicente Rocafuerte parish Victory. It was considered essential to respond to a problem that has become a critical issue in the educational establishment, where the lack of recreational teaching strategies have a negative impact on learning outcomes making activities and monotonous learning routine. In the research process and research methods they were used: analysis in the presentation of survey results, the synthesis of the conclusions; the statistical presentation of the results of scientific research and in the preparation of the final report. The results of the research process revealed the urgent need for a tutorial that guides teachers to develop musical intelligence of children at the same time it should become a tool for developing personal and human skills to discover the taste, motivation and sensitivity to musical art.